2018
DOI: 10.1061/(asce)cp.1943-5487.0000739
|View full text |Cite
|
Sign up to set email alerts
|

Stability Condition Identification of Rock and Soil Cutting Slopes Based on Soft Computing

Abstract: For transportation infrastructure, one of the greatest challenges today is to keep large-scale transportation networks, such as railway networks, operational under all conditions. This task becomes even more difficult to accomplish if taken into account budget limitations for maintenance and repair works. In this paper, it is presented a tool aimed at helping in management tasks related to maintenance and repair works for a particular element of this infrastructure, the slopes. The highly flexible learning cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Thus, by assessing features' relevance, both scholars and practitioners can discern what influences guest satisfaction, which can leverage decision making. This study proposes using the data-based sensitivity analysis (DSA), which was first introduced by Cortez and Embrechts (2013) and has since been applied to wide number of cases, including tourism (e.g., Moro et al, 2017), civil engineering (Tinoco et al, 2017), and marketing (Romão et al, 2019). The DSA takes a randomly selected sample of data from the training dataset, and then uses it by simultaneously varying the input features through their range of possible values to assess output sensitivity to such input changes (Cortez and Embrechts, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, by assessing features' relevance, both scholars and practitioners can discern what influences guest satisfaction, which can leverage decision making. This study proposes using the data-based sensitivity analysis (DSA), which was first introduced by Cortez and Embrechts (2013) and has since been applied to wide number of cases, including tourism (e.g., Moro et al, 2017), civil engineering (Tinoco et al, 2017), and marketing (Romão et al, 2019). The DSA takes a randomly selected sample of data from the training dataset, and then uses it by simultaneously varying the input features through their range of possible values to assess output sensitivity to such input changes (Cortez and Embrechts, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, determining whether a slope will fail or not is frequently a difficult task involving many variables and high dimensionality. In order to work around these kinds of restrictions and aid in the decision-making process for large-scale network management, a first endeavor was recently made [30,31] by comparing two popular types of data mining (DM) algorithms: artificial neural betworks (ANNs) [32,33] and support vector machines (SVMs) [34]. When compared with other simpler learning models (e.g., multiple regression or logistic regression models), the ANN and SVM models are more flexible learners, being capable of learning complex input-to-output mappings.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…When compared with other simpler learning models (e.g., multiple regression or logistic regression models), the ANN and SVM models are more flexible learners, being capable of learning complex input-to-output mappings. We particularly note that the two initial slope stability prediction studies [30,31] assumed a fixed set of selected input variables that could easily be collected during routine inspection activities. The main goal was to compare two learning models (ANN and SVM) for both regression and classification tasks.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…These advanced algorithms have been widely applied in different knowledge domains [23,24] with very promising results and taking advantage of a consolidated experience. In the field of Civil Engineering, several successful applications of these tools can be found [25][26][27], including solving complex geotechnical problems related to slopes stability assessment [28,29]. These algorithms have also been applied in the study of mechanical properties of soil-binder-water mixtures as reported on Tinoco et al [30], which underline the non-linear learning capabilities of these algorithms.…”
Section: Introductionmentioning
confidence: 99%